2015
DOI: 10.1515/cmam-2015-0008
|View full text |Cite
|
Sign up to set email alerts
|

On ℓ1-Regularization in Light of Nashed's Ill-Posedness Concept

Abstract: Abstract. Based on the powerful tool of variational inequalities, in recent papers convergence rates results on 1 -regularization for ill-posed inverse problems have been formulated in infinite dimensional spaces under the condition that the sparsity assumption slightly fails, but the solution is still in 1 . In the present paper we improve those convergence rates results and apply them to the Cesáro operator equation in 2 and to specific denoising problems. Moreover, we formulate in this context relationships… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…Wellposedness, however, does not exclude the case of non-injective A possessing non-trivial nullspaces N (A). We note that an analog to Definition 2 in Banach spaces, but only for injective A, has been discussed in the context of 1 -regularization in [9]. Proposition 1.…”
Section: Introductionmentioning
confidence: 99%
“…Wellposedness, however, does not exclude the case of non-injective A possessing non-trivial nullspaces N (A). We note that an analog to Definition 2 in Banach spaces, but only for injective A, has been discussed in the context of 1 -regularization in [9]. Proposition 1.…”
Section: Introductionmentioning
confidence: 99%
“…provides us with a variational inequality (13). Along the lines of the proof of [5, Theorem 5.2] one can show the assertion of the following lemma.…”
Section: Convergence Rates For 1 -Regularizationmentioning
confidence: 89%
“…In other words, for such operators there exist appropriate sequences {γn} n∈N occurring in (17) such that a variational source condition (13) holds for an index function ϕ from (17) and constant β = 1−µ 1+µ (see Proposition 5.5 below). Item (b) in Property 4.2 is a generalization of (9).…”
Section: (I)mentioning
confidence: 99%
See 1 more Smart Citation
“…Since the synthesis operator L : ℓ 1 (N) → X is injective and bounded, the linear operator A : ℓ 1 (N) → Y is also injective and bounded if A : X → Y is. In [12,Proposition 4.6] we have shown that the operator equation (1.1) with A = A • L as introduced above is always ill-posed, i.e. R(A) = R(A), and even ill-posed of type II in the sense of Nashed (cf.…”
Section: Introductionmentioning
confidence: 99%